A multilocular radiolucency of mandible as the first evidence of multiple myeloma: A clinico-radiographic case report - Ravi Prakash Sasankoti Mohan; Navneet Gill; Sankalp Verma; Venkateshwar Rao Chawa; Kuber Tyagi; Neha Agarwal (Wolters Kluwer Medknow Publications, 2014)
The incidence of multiple myeloma (MM) affecting the jaws is 30% and on rare occasions the oral involvement can be the first indication of the disease. Authors report a case of MM in a 40-year-old woman who presented with a multilocular radiolucent lesion in the left mandible initially mistaken as an ameloblastoma. Conventional radiographs revealed a multilocular lesion on the molar region. Computed tomography (CT) and 3 dimensional CT revealed lytic, space occupying lesion perforating the inferior cortex. Magnetic resonance imaging (MRI) revealed a hypointense lesion on T1 weighted image and hyperintense lesion on T2 weighted image. Histopathological and lab investigations lead to the diagnosis of MM. MRI is superior in depicting the size of the lesion as compared to CT and conventional radiographs.